A look at physical education from the motor praxiology: contributions, clarifications and applications (Impetus, 2022)
This essay presents and analyzes motor praxiology in the field of physical education, describing each one, in such a way that their differentiation is evident and their similarities understood, in order to better understand the direct and necessary relationship that motor praxiology has with education. physical. In this way, separating this sporting relationship that had been taking place and structuring, the path to where physical education and motor praxiology should cross, starting from the educational practices that occur in physical education and how these are directly related to praxiology motor, a theoretical and scientific approach to motor praxiology will be made in order to understand its relationship with educational practices and argue the intention of this essay, in the same way relevant aspects that permeate both concepts, such as sport and communication, will be touched. In this way, a complete and broad approach to the contributions and applications of motor praxiology to physical education will be given.
Keywords: Sport; physical education; motor skills; reflection